Schmitt and the Sovereignty of Roman Dictators: From the Actualisation of the Past to the Recycling of Symbols. Issue 1 (2nd January 2016) - Tuori, Kaius
SUMMARY: The aim of this article is to analyse the complex roots of Carl Schmitt's theory on dictatorship in the classical world through the lens of classical receptions. It argues that Schmitt was deeply engaged with the classical tradition in formulating his theory on dictatorship. Knowingly or unknowingly, Schmitt legitimates his theory through a foundation in both the Roman idealisation of the virtuous dictators of the early Republic as well as the long tradition of the narrative of the enlightened sovereign as a guarantor of law, present in both Greek and Roman antiquity and in the subsequent European tradition. Schmitt skilfully repurposed the Roman historical tradition on dictators but glossed over the traditional antipathy of Roman republicanism towards sovereign rule. The claim that this article is presenting is that even though it has been overlooked by earlier scholars, Schmitt was both directly and indirectly influenced by the classical tradition of dictatorship and utilised their mythical and symbolic dimensions in the later Roman and the subsequent European legal and political traditions. The reason for this omission was that Schmitt, like his contemporaries, belonged to one of the last generations to be groomed in the classical tradition of literature.